Neuronal-specific microexon splicing of TAF1 mRNA is directly regulated by SRRM4/nSR100. Issue 1 (2nd January 2020) - Capponi, Simona; Stöffler, Nadja; Irimia, Manuel; Van Schaik, Frederik M.A.; Ondik, Mercedes M.; Biniossek, Martin L.; Lehmann, Lisa; Mitschke, Julia; Vermunt, Marit W.; Creyghton, Menno P.; Graybiel, Ann M.; Reinheckel, Thomas; et al.
ABSTRACT: Neuronal microexons represent the most highly conserved class of alternative splicing events and their timed expression shapes neuronal biology, including neuronal commitment and differentiation. The six-nt microexon 34ʹ is included in the neuronal form of TAF1 mRNA, which encodes the largest subunit of the basal transcription factor TFIID. In this study, we investigate the tissue distribution of TAF1-34ʹ mRNA and protein and the mechanism responsible for its neuronal-specific splicing. Using isoform-specific RNA probes and antibodies, we observe that canonical TAF1 and TAF1-34ʹ have different distributions in the brain, which distinguish proliferating from post-mitotic neurons. Knockdown and ectopic expression experiments demonstrate that the neuronal-specific splicing factor SRRM4/nSR100 promotes the inclusion of microexon 34ʹ into TAF1 mRNA, through the recognition of UGC sequences in the poly-pyrimidine tract upstream of the regulated microexon. These results show that SRRM4 regulates temporal and spatial expression of alternative TAF1 mRNAs to generate a neuronal-specific TFIID complex.